Comparison of Ahmed glaucoma valve implantation and trabeculectomy for glaucoma: a systematic review and meta-analysis. - Tan HaiBo; Kang Xin; Lu ShiHeng; Liu Lin (PLoS ONE)
Objective To compare the efficacy and safety of Ahmed glaucoma valve implantation (AGV) with trabeculectomy in the management of glaucoma patients. Methods A comprehensive literature search (PubMed, Embase, Google, and the Cochrane library) was performed, including a systematic review with meta-analysis of controlled clinical trials comparing AGV versus trabeculectomy. Efficacy estimates were the weighted mean differences (WMDs) for the percentage intraocular pressure reduction (IOPR %) from baseline to end-point, the reduction in glaucoma medications, and the odds ratios (ORs) for complete and qualified success rates. Safety estimates were the relative risks (RRs) for adverse events. All outcomes were reported with a 95% confidence interval (CI). Statistical analysis was performed using the RevMan 5.0 software. Results Six controlled clinical trials were included in this meta-analysis. There was no significant difference between the AGV and trabeculectomy in the IOPR% (WMD = -3.04, 95% CI: -8.36- 2.26; P = 0.26). The pooled ORs comparing AGV with trabeculectomy were 0.46 (0.22, 0.99) for the complete success rate (P = 0.05) and 0.97 (0.78-1.20) for the quantified success rate (P = 0.76). No significant difference in the reduction in glaucoma medicines was observed (WMD = 0.24; 95% CI: -0.27-0.76; P = 0.35). AGV was found to be associated with a significantly lower frequency of all adverse events (RR = 0.71; 95%CI: 1.14-0.97; p = 0.001) than trabeculectomy, while the most common complications did not differ significantly (all p> 0.05). Conclusion AGV was equivalent to trabeculectomy in reducing the IOP, the number of glaucoma medications, success rates, and rates of the most common complications. However, AGV was associated with a significantly lower frequency of overall adverse events.